(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This research was carried out on the Gorontalo State University campus, using a qualitative research approach. defines that qualitative research is a research procedure that produces descriptive data in the form of written or spoken words from people and observed behavior. Using a qualitative approach, researchers describe the development of apparatus resources at the General and Financial Bureau of Gorontalo State University. The reason for using qualitative research methods is considered appropriate because of the suitability between the characteristics of qualitative research and the phenomena being studied. The use of this qualitative research method is directed at describing and analyzing the phenomenon of apparatus resource development at the General and Financial Bureau of Gorontalo State University. The relevance of using qualitative research methods can be understood because for each problem there are various phenomena that are specific and interrelated, including mechanisms, implementation and obstacles faced by local governments in developing apparatus resources. The results of the research can be concluded that Gorontalo State University as one of the State Universities in Gorontalo Province is not free from this problem. Gorontalo State University in improving the performance of its employees is faced with obstacles that arise, including the low level of understanding of employees’ main duties and functions in supporting the implementation of their duties. To support the implementation of existing tasks, each employee must always have a good understanding of what their main duties and responsibilities are.